PEMBERLAKUAN UPAH MINIMUM DALAM SISTEM PENGUPAHAN NASIONAL UNTUK MENINGKATKAN KESEJAHTERAAN TENAGA KERJA - Trimaya, Arrista (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2014)
The key issue of employment relations is wages, a monetary compensation provided by employer to employee in an employment relation stipulated in an employment agreement. Basically, payment of wages from employer to employee has to consider the three aspects of technical, economical, and legal. These three aspects are interrelated with each other and in its implementation, none can be removed. This study used literature study method. As an approach this method is intended to gathered materials, data, and all information related to wages. The results of this literature study concluded that there is a significant importance of an imposed wage system at national level. Wage determination system is necessary in order to assure employee’s paid wage is above the minimum subsistence wage. Wage regulation through national wage system is also aim at improving the welfare of work force, increasing productivity, and seeking equitable distribution of income in order to create social welfare.